Connecting short-range order for the liquid-solid transition of Al-Cu-Fe alloys. (December 2021) - Cao, Saichao; Zeng, Long; Xia, Mingxu; Yu, Pengfei; Xu, Mingqin; Ge, Xuan; Wang, Yun; Dhindaw, Brij Kumar; Lu, Wenquan; Fu, Yanan; Xie, Honglan; Li, Jianguo
Abstract: Liquid-solid transition processes have always been mysterious, especially those with the participation of quasicrystal (QC) structures, and are generally far less understood than the conventional solidification process. Here, the liquid structure variation of ternary QC-forming Al60 Cu37 Fe3 with crystal-forming Al50 Cu40 Fe10 alloy liquids was compared using synchrotron radiation based on high-energy X-ray diffraction (HE-XRD) and reverse Monte Carlo simulation (RMC). It was noted that the types of short-range order structures are almost the same in the Al60 Cu37 Fe3 and Al50 Cu40 Fe10 alloy liquids, while the former has more icosahedral short-range order (ISRO) and the latter has less. The medium-range order (MRO) was characterized by the cluster correlation method and visualization analysis. More obvious structural heterogeneity was found in the Al60 Cu37 Fe3 liquid, which is due to the strong correlation between clusters with high icosahedral order and the weak correlation between crystal clusters. Moreover, strongly correlated ISRO clusters can form icosahedral medium-range order (IMRO) structures by interpenetrating connections forming a stable structure upon cooling, and some other clusters can even enhance the IMRO stability. Such IMRO will be retained in the liquid upon cooling, leading to QC formation. All the findings provide a further understanding of the liquid-solid transition with ISRO participation. Graphical Abstract: ga1 Highlights: Solidification path selection relies on the connection tendency of ISRO. The connection between ISROs will enhance the stability of the orders. Icosahedral medium-range orders will lead to quasicrystals in liquid upon cooling.